Students' Perception of Communication Ethics in Social Media - ., Marjianto (Journal of Ecohumanism, 2024)
This study aims to describe students' perceptions of communication ethics on social media content and platforms. The approach used in this study is a qualitative descriptive approach. . Through the use of qualitative methods, more complete, certain, and reliable data collection techniques will be obtained through interviews, observations and questionnaires to students of Buddhist religious universities in Central Java. Students' perception of communication ethics in social media content includes written content, photos and videos, student perception states that social media users are in accordance with communication ethics. The percentage of student perceptions of written content stated that they agreed according to communication ethics by 79 percent, in photo content student perceptions agreed according to communication ethics by 57 percent, and in video students, perceived social media users according to communication ethics by 61 percent. Students' perception of users of social media platforms WharsApp, Instagram and Youtube mostly upholds communication ethics because more than fifty percent of students perceive it as such. Meanwhile, two platforms, namely Facebook and Tiktok, students perceive that most social media users do not uphold communication ethics.